Dynamic contact problems with velocity conditions - Chau, Oanh; Motreanu, Viorica Venera (Zielona Góra: Uniwersytet Zielonogórski)
We consider dynamic problems which describe frictional contact between a body and a foundation. The constitutive law is viscoelastic or elastic and the frictional contact is modelled by a general subdifferential condition on the velocity, including the normal damped responses. We derive weak formulations for the models and prove existence and uniqueness results.
Keywords: viscoelastic; elastic; subdifferential boundary condition; dynamic process; nonlinear hyperbolic variational inequality; maximal monotone operator; weak solution